2010
DOI: 10.1002/htj.20312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flow and Heat Transfer in a Parallelogram Non‐Uniformly Heated Enclosure Filled with Porous Medium

Abstract: The flow and heat transfer in a parallelogram enclosure filled with a porous medium is analyzed numerically. The heated bottom wall has a sinusoidal temperature distribution and side walls cooled isothermally while the upper wall is well insulated. Dimensionless Darcy law and energy equations are solved using the finite difference method along with the corresponding boundary condition. Computations were carried out for four inclination angles of side walls (γ = 45°, 60°, 75°, 90°) with different Rayleigh numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…He concluded that the heat transfer rate was increased by an increase in the thermal conductivity parameter and it was reduced in the presence of heat sources. Soleimani et al [24 ] analyzed numerically the flow and heat transfer in a parallelogram enclosure filled with a porous medium. The heated bottom wall had a sinusoidal temperature distribution and sidewalls cooled isothermally while the upper wall was well insulated.…”
mentioning
confidence: 99%
“…He concluded that the heat transfer rate was increased by an increase in the thermal conductivity parameter and it was reduced in the presence of heat sources. Soleimani et al [24 ] analyzed numerically the flow and heat transfer in a parallelogram enclosure filled with a porous medium. The heated bottom wall had a sinusoidal temperature distribution and sidewalls cooled isothermally while the upper wall was well insulated.…”
mentioning
confidence: 99%